Association between use of a health information exchange system and hospital admissions - Vest, J.R.; Kern, L.M.; Campion, T.R., Jr.; Silver, M.D.; Kaushal, R. (Applied Clinical Informatics, 2014)
Objective: Relevant patient information is frequently difficult to obtain in emergency department (ED) visits. Improved provider access to previously inaccessible patient information may improve the quality of care and reduce hospital admissions. Health information exchange (HIE) systems enable access to longitudinal, community-wide patient information at the point of care. However, the ability of HIE to avert admissions is not well demonstrated. We sought to determine if HIE system usage is correlated with a reduction in admissions via the ED.Methods: We identified 15,645 adults from New York State with an ED visit during a 6-month period, all of whom consented to have their information accessible in the HIE system, and were continuously enrolled in two area health plans. Using claims we determined if the ED encounter resulted in an admission. We used the HIE’s system log files to determine usage during the encounter. We determined the association between HIE system use and the likelihood of admission to the hospital from the ED and potential cost savings.Results: The HIE system was accessed during 2.4% of encounters. The odds of an admission were 30% lower when the system was accessed after controlling for confounding (odds ratio = 0.70; 95%C I= 0.52, 0.95). The annual savings in the sample was $357,000.Conclusion: These findings suggest that the use of an HIE system may reduce hospitalizations from the ED with resultant cost savings. This is an important outcome given the substantial financial investment in interventions designed to improve provider access to patient information in the US.Citation: Vest JR, Kern LM, Campion TR Jr, Silver MD, Kaushal R. Association between use of a health information exchange system and hospital admissions. Appl Clin Inf 2014; 5: 219–231 http://dx.doi.org/10.4338/ACI-2013-10-RA-0083
Keywords: Health information exchange; computerized patient records; information systems; emergency department; admission